The impact of maternally derived immunity on influenza A virus transmission in neonatal pig populations - Allerson, Matt (2012)
The commonality of influenza A virus (IAV) exposure and vaccination on swine farms in the United States ensures that the majority of neonatal pigs will have some degree of maternal immunity to IAV. The influence of maternal immunity on IAV transmission in neonatal pig populations will impact virus prevalence and infection dynamics across pig populations. The main objective of this study was to assess the impact of maternally derived immunity on IAV transmission in an experimental setting. Neonatal pigs suckled colostrum and derived maternal (passive) immunity from sows in one of three treatment groups: a) non-vaccinated control (CTRL) or vaccinated with b) homologous (PASSV-HOM) or c) heterologous (PASSV-HET) inactivated experimental IAV vaccines. Sentinel neonatal pigs derived from the groups above were challenged with IAV via direct contact with an experimentally infected pig (seeder pig) and monitored for IAV infection daily via nasal swab sampling. A Susceptible-Infectious-Recovered (SIR) experimental model was used to obtain and estimate transmission parameters in each treatment group via a generalized linear model. All sentinel pigs in the CTRL (30/30) and PASSV-HET (30/30) groups were infected with IAV following contact with the seeder pigs and the reproduction ratio estimates were 10.4 (6.6–15.8) and 7.1 (4.2–11.3), respectively. In contrast, 1/20 sentinel pigs in the PASSV-HOM group was infected following contact with the seeder pigs and the reproduction ratio estimate was significantly lower compared to the CTRL and PASSV-HET groups at 0.8 (0.1–3.7). Under the conditions of this study, IAV transmission was reduced in neonatal pigs with homologous maternal immunity compared to seronegative neonatal pigs and pigs with heterologous maternal immunity as defined in this study. This study provides estimates for IAV transmission in pigs with differing types of maternal immunity which may describe the influence of maternal immunity on IAV prevalence and infection dynamics in pig populations.